Tyrosine kinase inhibitors as an alternative treatment in canine mast cell tumor - Coelho, Yasmin Nascimento Bernardes; Soldi, Luiz Ricardo; Silva, Paulo Henrique Rosa da; Mesquita, Caio Melo; Paranhos, Luiz Renato; Santos, Thaísa Reis dos; Silva, Marcelo José Barbosa (Frontiers in Veterinary Science, 2023)
The current gold standard treatment for canine mast cell tumors (MCT) uses vinblastine sulfate (VBL) as chemotherapy, although tyrosine kinase inhibitors (TKI) have recently been shown to be worthy candidates for treatment. This systematic review aimed to analyze the overall survival (OS), progression-free survival (PFS), overall response rate (ORR), and complete (CR) or partial response (PR) in dogs with MCT treated with TKI compared to standard VBL treatment. An electronic search was performed in nine databases. References from eligible studies were also selected to find more registers. A total of 28 studies met the eligibility criteria, and one more was recovered from the references of eligible studies, totaling 29 selected studies. The overall survival and progression-free survival of vinblastine-treated dogs were higher compared to tyrosine kinase inhibitors-treated dogs. However, dogs with mutated KIT treated with tyrosine kinase inhibitors have longer overall survival and progression-free survival compared to those treated with vinblastine. The overall response rate, complete response, and, partial response were higher in dogs treated with tyrosine kinase inhibitors than in dogs treated with vinblastine. Standard treatment with VBL showed greater clinical benefits than tyrosine kinase inhibitors in terms of overall survival and progression-free survival, however, in the TKI group, dogs with c-kit mutation demonstrate superior benefits when compared to the vinblastine group.